Agents and Multi-Agent Systems: Technologies and Applications 2018 Proceedings of the 12th International Conference on Agents and Multi-Agent Systems: Technologies and Applications (KES-AMSTA-18) - Jezic, Gordan; Chen-Burger, Yun-Heh Jessica; Howlett, Robert J.; Jain, Lakhmi C.; Vlacic, Ljubo; Šperka, Roman (Smart Innovation, Systems and Technologies, 2019)
This book highlights new trends and challenges in agent systems, and new digital and knowledge economy research, and includes 34 papers on areas such as intelligent agent interaction and collaboration, modeling, simulation and mobile agents, agent communication and social networks, business Informatics, design and implementation of intelligent agents and multi-agent systems. These papers were presented at the 12th International KES Conference on Agents and Multi-Agent Systems: Technologies and Applications (KES-AMSTA 2018) held on Australia's Gold Coast. The modern economy is driven by technologies and knowledge. Digital technologies can free, shift and multiply choices, often intruding on the space of other industries, by providing new ways of conducting business operations and creating values for customers and companies. The book addresses topics that contribute to the modern digital economy, including software agents, multi-agent systems, agent modeling, mobile and cloud computing, big data analysis, business intelligence, artificial intelligence, social systems, computer embedded systems and nature inspired manufacturing, which contribute to the modern digital economy. The results presented are of theoretical and practical value to researchers and industrial practitioners working in the fields of artificial intelligence, collective computational intelligence, innovative business models, new digital and knowledge economy and, in particular, agent and multi-agent systems, technologies, tools and applications.